(untitled) (Research, Society and Development, 2021)
Brazilian traffic is chaotic and has a high accident rate, mainly influenced by: 1 – Road conditions; 2 – Climate and 3 – Population growth. There are several definitions of accidents, among them we have: unintentional event and unpremeditated event. Knowing that this problem affects several capitals in the country, Belém was chosen for having major problems in all its urban mobility. Therefore, the objective is to statistically analyze the spatial occurrences of traffic accidents in 2017, considering: neighborhoods and streets; in order to plot thematic maps on the respective analysis. The methodology used was: 1 - the collection of raw data with the Executive Superintendence of Urban Mobility of Belém (SeMOB); 2 - use of Excel software to analyze the variables and 3 - application in ArcGIS 10.1 Software in order to systematically plot thematic maps, requiring consistent results on the problem for easy understanding and representation through thematic illustrations, informing critical regions of occurrences and the variables that most influenced the data, as well as discussing the results observed with the current city scenario.